A thermoregulation model for hypothermic treatment of neonates. Issue 9 (September 2016) - Silva, Ana Beatriz C.G.; Laszczyk, Joanna; Wrobel, Luiz C.; Ribeiro, Fernando L.B.; Nowak, Andrzej J.
Highlights: Thermoregulation model to simulate hypothermia procedures. Applied for the treatment of encephalopathy hypoxic-ischemia in neonates. Blood temperature changes considered using a hemodynamic model. Results show that the model can be used to study different cooling procedures. May lead to optimization of hypothermic treatment on a patient-specific basis. Abstract: This paper presents a thermoregulation finite element model (FEM) to simulate hypothermia procedures for the treatment of encephalopathy hypoxic-ischemia (EHI) in neonates, a dangerous ischemic condition that can cause neurological damages and even death. Therapeutic hypothermia is the only recommended technique to reduce sequels caused by EHI in neonates; intervention with moderate cooling for neural rescue in newborns with hypoxic-ischemic brain injury is the culmination of a series of clinical research studies spanning decades. However, the direct monitoring of brain cooling is difficult and can lead to additional tissue damage. Therefore, the measurement of efficiency during clinical trials of hypothermia treatment is still challenging. The use of computational methods can aid clinicians to observe the continuous temperature of tissues and organs during cooling procedures without the need for invasive techniques, and can thus be a valuable tool to assist clinical trials simulating different cooling options that can be used for treatment. The use of low cost methods such as cooling blankets can open the possibility of using brain cooling techniques in hospitals and clinics that cannot currently afford the available expensive equipment and techniques. In this work, we developed a FEM package using isoparametric linear three-dimensional elements which is applied to the solution of the continuum bioheat Pennes equation. Blood temperature changes were considered using a blood pool approach. The results of the FEM model were compared to those obtained through the implementation of a user-defined function (UDF) in the commercial finite volume software FLUENT and validated with experimental tests. Numerical analyses were performed using a three-dimensional mesh based on a complex geometry obtained from MRI scan medical images.